2014
DOI: 10.1016/j.febslet.2014.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Netrin‐4 derived from murine vascular endothelial cells inhibits osteoclast differentiation in vitro and prevents bone loss in vivo

Abstract: a b s t r a c tBone is a highly vascularized organ, thus angiogenesis is a vital process during bone remodeling. However, the role of vascular systems in bone remodeling is not well recognized. Here we show that netrin-4 inhibits osteoclast differentiation in vitro and in vivo. Co-cultures of bone marrow macrophages with vascular endothelial cells markedly inhibited osteoclast differentiation. Adding a neutralizing antibody, or RNA interference against netrin-4, restored in vitro osteoclast differentiation. Ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 36 publications
0
30
0
Order By: Relevance
“…3, G-I). Other than netrin 1, osteoblasts produce osteoclast inhibitory axon guidance factors such as Sema3A (24), EphB4 (25), and netrin 4 (26). A comparison of these axon guidance factors showed that netrin 1 was the most potent inhibitor of osteoclastogenesis (Fig.…”
Section: Netrin 1 Is Expressed In Osteoblasts Andmentioning
confidence: 99%
“…3, G-I). Other than netrin 1, osteoblasts produce osteoclast inhibitory axon guidance factors such as Sema3A (24), EphB4 (25), and netrin 4 (26). A comparison of these axon guidance factors showed that netrin 1 was the most potent inhibitor of osteoclastogenesis (Fig.…”
Section: Netrin 1 Is Expressed In Osteoblasts Andmentioning
confidence: 99%
“…Affinity‐purified rabbit polyclonal antibody specific for Cryba4 was raised against the synthetic peptide with the sequence HSGDYKHFREWGSH (Eurofins Genomics K.K., Tokyo, Japan). cDNAs from mouse lens, mouse Achilles tendon and mouse masseter muscle and tendon were prepared as described in a previous paper (Enoki et al., ).…”
Section: Methodsmentioning
confidence: 99%
“…We have previously demonstrated that Ntn4, derived from vascular endothelial cells inhibits osteoclast differentiation (13). We speculate that netrin family may play a vital role for bone metabolism.…”
Section: Discussionmentioning
confidence: 83%
“…To validate changes in gene expression, quantitative real time RT-PCR (qPCR) analysis was performed using Applied Biosystems Prism 7900HT Sequence Detection System according to the manufacturer's instructions (Thermo Scientific, Wilmington, DE, USA) as previously described (13). Total RNA was extracted from cells using ISOGEN (Nippon Gene, Tokyo, Japan).…”
Section: Quantitative Reverse-transcriptase Polymerase Chain Reactionmentioning
confidence: 99%
See 1 more Smart Citation